Molecular mechanism of protrusion formation during cell-to-cell spread of Listeria - Ireton, Keith; Rigano, Luciano A.; Polle, Lilia; Schubert, Wolf-Dieter (Frontiers in Cellular and Infection Microbiology, 2014)
The bacterial pathogen Listeria monocytogenes spreads within human tissues using a motility process dependent on the host actin cytoskeleton. Cell-to-cell spread involves the ability of motile bacteria to remodel the host plasma membrane into protrusions, which are internalized by neighboring cells. Recent results indicate that formation of Listeria protrusions in polarized human cells involves bacterial antagonism of a host signaling pathway comprised of the scaffolding protein Tuba and its effectors N-WASP and Cdc42. These three human proteins form a complex that generates tension at apical cell junctions. Listeria relieves this tension and facilitates protrusion formation by secreting a protein called InlC. InlC interacts with a Src Homology 3 (SH3) domain in Tuba, thereby displacing N-WASP from this domain. Interaction of InlC with Tuba is needed for efficient Listeria spread in cultured human cells and infected animals. Recent structural data has elucidated the mechanistic details of InlC/Tuba interaction, revealing that InlC and N-WASP compete for partly overlapping binding surfaces in the Tuba SH3 domain. InlC binds this domain with higher affinity than N-WASP, explaining how InlC is able to disrupt Tuba/N-WASP complexes.